THE IMPROVEMENT IN THE QUALITY OF LEARNING IN EUROPE’S HIGHER EDUCATION INSTITUTIONS - Madlena NEN (Management & Marketing)
A major aim of Bologna processes it to increase the mobility of students and teachers. The Diploma Supplement, the ECTS, Europass, Youthpass and the harmonization of the structure of higher education are several measures that can have a positive impact on students’ mobility. Nowadays, more and more students decide to spend a part of their studies in another foreign university for some days, months or years. The current study aims at elaborating an in-depth analysis of the conditions for outgoing students from Romania within Erasmus activities under Life Long Learning Programme as well as the impact of these mobilities on personal and career development., The participation to mobility programs (among which Erasmus programme plays a major role) has been constantly growing in the last year instead of a series of difficulties: (administrative and financial constraints, information and communication constraints, obstacles in recognition of the studies period abroad).